2022
DOI: 10.1093/advances/nmab127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidants on Sperm Quality Parameters in Subfertile Men: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: Antioxidant supplementation has been identified as an important intervention for subfertile men. However, the effectiveness of different antioxidants in improving sperm quality remains unclear. In this study, a network meta-analysis (NMA) was designed to evaluate the effects of different antioxidants on sperm quality parameters in subfertile men. Published randomized controlled trials (RCTs) of antioxidants in subfertile men were searched in the PubMed, Embase, and Cochrane Library databases from inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
3
4
0
1
Order By: Relevance
“…This approach is obviously not comparable with that used in our NMA, where the analysis was restricted to antioxidant treatments in men with idiopathic OAT. In the NMA by Su et al, 89 more comparable in design with our NMA, CoQ10 and carnitine showed better efficacy in increasing sperm concentration and sperm motility, respectively. The lack of effect of CoQ10 on sperm concentration in our analysis may partly depend on the exclusion of the Safarinejad trials, 65,68 which were instead included in the NMA by Su et al 89 In addition, while in the NMA of Su et al 89 oligozoospermia, asthenozoospermia, or teratozoospermia were considered as a single condition, in our NMA, as a major strength, improvement of each seminal parameter was quantified only in the series that exhibited an alteration of that particular parameter at baseline.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This approach is obviously not comparable with that used in our NMA, where the analysis was restricted to antioxidant treatments in men with idiopathic OAT. In the NMA by Su et al, 89 more comparable in design with our NMA, CoQ10 and carnitine showed better efficacy in increasing sperm concentration and sperm motility, respectively. The lack of effect of CoQ10 on sperm concentration in our analysis may partly depend on the exclusion of the Safarinejad trials, 65,68 which were instead included in the NMA by Su et al 89 In addition, while in the NMA of Su et al 89 oligozoospermia, asthenozoospermia, or teratozoospermia were considered as a single condition, in our NMA, as a major strength, improvement of each seminal parameter was quantified only in the series that exhibited an alteration of that particular parameter at baseline.…”
Section: Discussionsupporting
confidence: 64%
“…This approach is obviously not comparable with that used in our NMA, where the analysis was restricted to antioxidant treatments in men with idiopathic OAT. In the NMA by Su et al., 89 more comparable in design with our NMA, CoQ10 and carnitine showed better efficacy in increasing sperm concentration and sperm motility, respectively. The lack of effect of CoQ10 on sperm concentration in our analysis may partly depend on the exclusion of the Safarinejad trials, 65,68 which were instead included in the NMA by Su et al 89 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Frontiers in Pharmacology frontiersin.org improve sperm motility (Su et al, 2021). Nevertheless, SNGPX4 KO mice have normal survival and fertility.…”
Section: Gpx4mentioning
confidence: 99%